The Effect of Leadership Style, Work Environment and Performance Benefits on Employee Performance in BP3TKI Office, Indonesia using Statistical Method - Rizal Saragih; Warjio Warjio; Susanti Susanti (Mahesa Research Center, 2021)
This study aims to determine the effect of leadership style, work environment and performance benefits on employee performance at the Service Office for Placement and Protection of Indonesian Migrant Workers (BP3TKI) Medan. The effect of these variables on employee performance was studied using statistical analysis. The sampling technique used in this study is saturated sampling. Scaled surveys has been done by 116 employees of Service Office for Placement and Protection of Indonesian Migrant Workers (BP3TKI) Medan. The statistical tool used is the Structural Equation Modelling (SEM), and analysed using LISREL 8.80 statistic software. The model developed fulfil Goodness of Fit (GoF) requirements from LISREL 8.80 to which shows that it is good enough. The most significant sub-variables are no strong grip and low confidence from leader, legislations related to employee’s performance benefits, and good air circulations in the workspace, which strongly affect work quality, time efficiency, and cooperation from employees in Medan BP3TKI office. For further research, other researchers, institutions, or parties, could use this research conclusion and suggestions as foundation or additional information for similar problems, that is to improve employee performance in an office.